Mobilizing device-mediated contributions in interaction involving beginner users of eye-gaze-accessed speech-generating devices. (9th December 2021) - Tegler, Helena; Demmelmaier, Ingrid; Blom Johansson, Monica; Norén, Niklas
Abstract : Interaction mediated by speech-generating devices (SGDs) may promote participation and independence for non-speaking children, but developing skills to use the SGD is time consuming and demanding. The present conversation analysis study aimed to identify features of interactional projects that mobilized SGD-mediated responses by two children with intellectual disability who were beginner-level users. The children and their professional communication partners were video recorded when interacting in an institutional setting. The analysis shows that SGD-mediated responses were mobilized by multimodal and sequentially organized actions combining different types of spoken initiatives, SGD modelling, and embodied resources that facilitated SGD use and hence participation. These results indicate a need for communication partners to use a wide range of practices to facilitate SGD-mediated interaction.